2004
DOI: 10.1136/jnnp.2003.024364
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected decline in survival from amyotrophic lateral sclerosis/motor neurone disease

Abstract: Objectives: To describe survival of 1226 Scottish adults with amyotrophic lateral sclerosis/motor neurone disease (ALS/ MND). Methods: Ten year, prospective, population based disease register. Cox time dependent proportional hazards modelling for multivariate survival analyses. Results: Median survival from onset was 25 months (interquartile range 16-34 months). In multivariate models we found an increased hazard with more recently diagnosed cases-that is, there was an unexpected decline in survival over the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 12 publications
5
32
1
1
Order By: Relevance
“…Generally, the risk of death of bulbar onset ALS is 4.5-fold higher (RR: 4.56, p=0.0007) than that of spinal onset ALS [20,22]. One reason for this finding is malnutrition [12,23], and as shown in this study, the BMI was significantly lower in bulbar onset patients (Table 1).…”
Section: Discussionsupporting
confidence: 54%
“…Generally, the risk of death of bulbar onset ALS is 4.5-fold higher (RR: 4.56, p=0.0007) than that of spinal onset ALS [20,22]. One reason for this finding is malnutrition [12,23], and as shown in this study, the BMI was significantly lower in bulbar onset patients (Table 1).…”
Section: Discussionsupporting
confidence: 54%
“…Cases with FTLD-MND also had a very short survival, with disease duration on average 2 to 3 years, similar to that of amyotrophic lateral sclerosis (ALS). 36 This is to be expected, since the motor neuron degeneration and other pathologic findings in FTLD-MND are similar to those in ALS where survival is about 3 years. 37 After pathologic reexamination, we did not have any cases of DLDH, unlike a recent clinicopathologic series.…”
Section: Figure 1 Pick Complex Can Be Divided Into Clinical Syndromementioning
confidence: 78%
“…A retrospective study with 1,226 patients with ALS showed a median survival time of 25 months (range: 16-34 months) and described an age difference, benefiting younger patients on clinical presentation, survival rate and functional independence 13 . Mandrioli et al 7 , Zoccolella et al 15 and Lee et al 6 also associated a greater age with a lower survival rate.…”
Section: Epidemiological Characteristicsmentioning
confidence: 99%
“…The patient may experience fatigue, gait instability, changes in speed or rhythm during speech, and a weak hand grip. Survival time after diagnosis is variable in the literature ( from eight to 66 months) 5,6,7,9,10,11,12,13,14,15,16,17,18,19,20,21,22 . In general, shorter intervals from symptom onset to diagnosis predict lower survival rates.…”
mentioning
confidence: 99%